Ethical dimensions of zoonotic disease research: Perspectives of traditional livestock keepers in Zambia [version 2; peer review: 2 approved] - Michelo Syakalima; Victor Chisha Zulu; Joseph Ali (Wellcome Open Research, 2023)
Background: With the increase in zoonotic disease research using livestock belonging to traditional livestock keepers (LKs) as research subjects, careful attention to both animal and livestock keeper interests is critically important in Zambia and other similar contexts. Methods: The study aimed to explore ethics-related challenges during zoonotic disease research among LKs where their livestock are included as research subjects. The study was implemented in the Southern province of Zambia in July 2020.  Three focus group discussions  (FGDs) involving 30 adult male LKs living in livestock-wildlife interface areas where zoonotic diseases are likely to occur, were carried out. The FGDs were done in the local language and audio recorded. Thematic analysis was done using field notes and translated and transcribed recorded interviews.  Results: The study found that trust between the researchers and LKs when their livestock are used as research subjects was very cardinal and depended on the continual presence of the local veterinary assistant (VA) during the conduct of research.  Conclusions: The LKs could be considered a vulnerable population when their livestock were used as research subjects as, being resource poor, they were looking to researchers to provide benefits yet not fully understanding the research, and thus did not worry so much about consent procedures, bringing into question the validity of the oral consent obtained. The study also found that opportunities to strengthen trust and enhance the research experience could be exploited by researchers conducting research that is locally relevant and desired, being aware of procedural preferences for entering into livestock keeping communities, adequate disclosure of research procedures, respecting conventions and traditional cultural beliefs, and returning results of research. The findings of this study can be used by both researchers as they carry-out zoonotic disease research and by Research Ethics Committees.